A practical methodology to evaluate internationally consistent energy data for China's transport sector. (1st December 2019) - Liu, Junling; Chen, Xirui; Zhou, Haiwei; Wang, Ke; Zou, Ji; Kong, Ying
Abstract: Because China's statistical system differs from other countries, the reported energy data of its transport sector cannot be used for worldwide comparison, representing an obstacle for scientific research and policy making. A practical methodology to evaluate internationally consistent energy data for China's transport sector is presented in this paper. A calibration process was used to combine the results from top-down and bottom-up methods. The results indicate that the total energy consumption related to all transport activities is about one-third higher than the officially reported data. Gasoline and diesel used by non-operating vehicles in the road sector represent the greatest difference. Total energy demand in China's transport sector was 327 million tons of coal equivalent (Mtce) in 2010, 411 Mtce in 2013, and 452 Mtce in 2015. After adjustment, the transport sector accounted for 13% of the total final energy demand in 2010 and 2013, 14% in 2015, and 10% of national CO2 emissions in 2015. During 2010–2013 and 2013–2015, total energy demand in China's transport sector increased by 84 Mtce and 41 Mtce, respectively, and 88% and 85% of the growth came from the road sector. Without calibration, bottom-up methods often resulted in an overestimation of energy consumption for gasoline and diesel, sometimes exceeding the total national consumption level. The proposed method and estimated results not only support the development of energy consumption and CO2 emission inventories for China but also lay the foundation for further research on low-carbon strategies for China's transport sector and associated policies. Uncertainties in the estimations and suggestions for improvement are also discussed. Highlights: Official data underestimated the energy demand in China's transport sector. A methodology to evaluate energy data for China's transport sector was introduced. Energy demand and CO2 emissions in transport in 2010, 2013 and 2015 were evaluated. Total energy demand of transport sector was one-third higher than official data. The reliability of evaluation result was substantially improved by this method.